Temporal Lobectomy for Intractable Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The results of temporal lobectomy in 16 children under the age of 12 years who had intractable seizures of temporal lobe origin are reported from the Miami Children's Hospital, Florida.